"I am years seven old." Acquisition of English word order by Bosnian and Turkish children - Akbarov, Azamat; Äapo, Larisa (English Studies at NBU, 2016)
This paper aims to investigate differences in the acquisition of English word order between Bosnian and Turkish students resulting from word order in these two languages (Bosnian and Turkish). In second language acquisition, the knowledge of the native language (L1) in acquisition of a foreign language (L2) can indeed have a facilitating or inhibiting effect on the learner’s progress in mastering a new language. Thirty children from the first grade at the International School of Sarajevo were tested. Some of them attended the kindergarten where English was a language of communication and the rest of them had six months of exposure of English in school settings. We wanted to find possible differences in acquiring word order in English in these groups of children as well. This study offers new results for acquiring correct word order in English.